Simultaneous Determination of Saponins in Radix Glycyrrhizae, Notoginseng and Ginseng by High Performance Liquid Chromatography - 张立国 方聪颖 欧阳霄雯 倪力军 (Transactions of Tianjin University, 2013)
To establish a method for determining five saponins（notoginsenoside R1, ginsenoside Rg1, ginsenoside Re, ginsenoside Rb1 and ammonium glycyrrhizinate） in Glycyrrhizae, Notoginseng and Ginseng, the high performance liquid chromatography with diode array detector（HPLC-DAD） method was applied to an Inertsil ODS-SP column（4.6 mm×250 mm, 5 μm） with a mobile phase consisting of acetonitrile-0.05% phosphoric acid in a gradient elution manner. The flow rate was 1.0 mL/min. The column temperature was 30 ℃ and the detection wavelengths were 203 nm and 237 nm, respectively. The linear ranges were 0.700,0—7.000,0 μg for R1（r=1.000,0）, 0.751,1— 7.511,4 μg for Rg1（r=1.000,0）, 0.677,2—6.771,6 μg for Re（r=1.000,0）, 0.733,9—7.339,1 μg for Rb1（r= 1.000,0）, and 0.540,0—5.399,8 μg for ammonium glycyrrhizinate（r=0.999,9）, respectively. In addition, their average recoveries were 100.28%, 105.83%, 104.09%, 99.36% and 98.54%, respectively. The relative standard deviations（RSDs） of precision, reproducibility and recovery were all less than 1.5%. The results indicate that the method is simple, accurate and reproducible so that it can be used for the simultaneous determination of the five saponins in Chinese patent medicines containing the three kinds of herbs.